The MPEG Handbook: MPEG-1, MPEG-2, MPEG-4 - Watkinson, John (Routledge, 2001)
A complete, professional 'bible' on all aspects of audio and video compression using MPEG technology, including the MPEG-4 standard and, in this second edition, H-264. The clarity of explanation and depth of technical detail combine to make this book an essential and definitive reference work.THE MPEG HANDBOOK is both a theoretical and practical treatment of the subject. Fundamental knowledge is provided alongside practical guidance on how to avoid pitfalls and poor quality. The often-neglected issues of reconstructing the signal timebase at the decoder and of synchronizing the signals in a multiplex are treated fully here.Previously titled MPEG-2, the book is frequently revised to cover the latest applications of the technology.